PENGOLAHAN PANGAN DENGAN PENAMBAHAN BAHAN KIMIA NATRIUM BENZOAT - Sebayang, Nico Syahputra; Alhanannasir, Alhanannasir; Murtado, Asep Dodo; Restyaningsih, Mega Bella; Yuliana, Intan; Dini, Chantika; Adriansyah, Reza; Madinah, Birral Mahdiyal; Silvyana, Silvyana (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
The addition of food chemicals is an activity in food processing. The addition of food chemicals in the food industry aims to improve quality, extend shelf life, and maintain product safety and taste. One of the additives that is often used is sodium benzoate. sodium salts from benzoic acid. Sodium benzoate serves as a preservative that prevents the growth of microorganisms, especially fungi and some types of bacteria, which can cause damage to food products. The use of sodium benzoate as a preservative has been widely recognized, especially in products with high water content and susceptible to microbial contamination, such as soft drinks, sauces, jams, and other processed foods. The method used for the creation of this review article is a literature study